Sealing sheet

By employing a cross-linked structure in the first and second moisture-absorbing layers of the sealing sheet, which contain olefin polymers and calcium oxide respectively, the problem of water vapor intrusion caused by hydrotalcite is solved, achieving a highly efficient barrier and transparent sealing effect.

CN115558342BActive Publication Date: 2026-11-03AJINOMOTO CO INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210758108.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-07-01
Filing Date
2022-06-30
Publication Date
2026-11-03
Estimated Expiration
2042-06-30

AI Technical Summary

Technical Problem

In existing sealing sheets, the water absorption and release phenomena of hydrotalcite lead to the deterioration of electronic devices and cannot effectively prevent water vapor from entering.

Method used

A sealing layer consisting of a first moisture-absorbing layer and a second moisture-absorbing layer is used. The first moisture-absorbing layer contains olefin polymers and semi-calcined hydrotalcite, and the second moisture-absorbing layer contains olefin polymers and calcium oxide. Through cross-linking structure and direct contact, moisture is captured, forming a transparent and highly efficient sealing layer that blocks water vapor.

Benefits of technology

It achieves the formation of a highly efficient water vapor barrier in electronic devices, suppressing adverse conditions caused by moisture and maintaining transparency and airtightness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003723275870000161
    Figure BDA0003723275870000161
  • Figure BDA0003723275870000281
    Figure BDA0003723275870000281
  • Figure BDA0003723275870000291
    Figure BDA0003723275870000291
Patent Text Reader

Abstract

The present application provides a sealing sheet that can form a sealing layer having excellent water vapor intrusion resistance in sealing of electronic devices and the like. A sealing sheet is a sealing sheet having a laminated structure including a support and a sealing layer, wherein the sealing layer is composed of a first moisture absorbing layer and a second moisture absorbing layer, the first moisture absorbing layer contains (A) an olefin-based polymer and (B) a semi-calcined hydrotalcite, and the second moisture absorbing layer contains (C) an olefin-based polymer and (D) calcium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to sealing sheets that can be used for sealing electronic devices and the like. Background Technology

[0002] To protect electronic devices such as organic EL (electroluminescence) devices and solar cells from moisture, an operation is performed to seal the electronic devices using a sealing layer formed from a sealing composition or a sealing sheet. For example, Patent Document 1 discloses a sealing resin composition comprising (A) a polyolefin resin and (B) a metal hydroxide selected from hydrotalcite and semi-calcined hydrotalcite, and a sealing sheet formed therefrom. However, hydrotalcite reversibly absorbs and releases moisture. Therefore, for sealing sheets using hydrotalcite, moisture absorbed by the hydrotalcite during the manufacturing process or distribution may be released in the sealing layer of the electronic device formed using that sheet, potentially leading to deterioration of the electronic device.

[0003] Existing technical documents Patent documents Patent Document 1: International Publication No. 2017 / 057708. Summary of the Invention

[0004] The technical problem that the invention aims to solve The object of the present invention is to provide a sealing sheet that can form a sealing layer with excellent water vapor intrusion barrier properties in the sealing of electronic devices and the like.

[0005] Technical solutions adopted to solve technical problems The present invention that achieves the above objectives is as follows; [1] A sealing sheet having a laminated structure comprising a support and a sealing layer, wherein... The sealing layer consists of a first moisture-absorbing layer and a second moisture-absorbing layer. The first absorbent layer comprises the following components (A) and (B): (A) Olefin polymers, and (B) Semi-calcined hydrotalcite; and The second absorbent layer contains the following components (C) and (D): (C) Olefin polymers, and (D) Calcium oxide; [2] According to the sealing sheet described in [1] above, wherein the (C) component in the second moisture-absorbing layer contains an olefin polymer having an anhydride group and / or a carboxyl group, and the median particle size of the (D) component in the second moisture-absorbing layer is 1 to 300 nm. [3] According to the sealing sheet described in [2] above, wherein the olefin polymer containing an anhydride group and / or carboxyl group in component (C) of the second moisture-absorbing layer is an olefin polymer containing an anhydride group; [4] According to the sealing sheet described in [2] or [3] above, wherein component (C) in the second moisture-absorbing layer comprises an olefin polymer having an epoxy group; [5] According to the sealing sheet described above [4], wherein the olefin polymer containing an anhydride group and / or carboxyl group in component (C) of the second moisture-absorbing layer forms a cross-linked structure with an olefin polymer containing an epoxy group; [6] The sealing sheet according to any one of [1] to [5] above, wherein the first moisture-absorbing layer and the second moisture-absorbing layer are in direct contact; [7] The sealing sheet according to any one of [1] to [6] above, wherein the content of component (B) is 10 to 80% by mass relative to the first moisture-absorbing layer as a whole; [8] The sealing sheet according to any one of [1] to [7] above, wherein the content of component (D) is 10 to 80% by mass relative to the second moisture-absorbing layer as a whole; [9] The sealing sheet according to any one of [1] to [8] above, wherein component (A) in the first moisture-absorbing layer comprises an olefin polymer having an anhydride group and / or a carboxyl group, and an olefin polymer having an epoxy group;

[10] According to the sealing sheet described in [9] above, wherein the olefin polymer containing an anhydride group and / or carboxyl group in component (A) of the first moisture-absorbing layer is an olefin polymer containing an anhydride group;

[11] According to the sealing sheet described in [9] or

[10] above, wherein the olefin polymer containing an anhydride group and / or carboxyl group in component (A) of the first moisture-absorbing layer forms a cross-linked structure with an olefin polymer containing an epoxy group;

[12] The sealing sheet according to any one of [1] to

[11] above, wherein one or both of component (A) in the first moisture-absorbing layer and component (C) in the second moisture-absorbing layer comprise a liquid olefin polymer;

[13] The sealing sheet according to any one of [1] to

[12] above, wherein one or both of the first moisture-absorbing layer and the second moisture-absorbing layer contain an adhesive agent;

[14] The sealing sheet according to any one of [1] to

[13] above, wherein the thickness of the sealing layer is 3 to 200 μm;

[15] The sealing sheet according to any one of [1] to

[14] above, wherein the ratio of the thickness of the second moisture-absorbing layer to the thickness of the first moisture-absorbing layer (thickness of the second moisture-absorbing layer / thickness of the first moisture-absorbing layer) is 0.05 to 2.0;

[16] The sealing sheet according to any one of [1] to

[15] above, wherein the haze of the sealing layer is less than 60%;

[17] An electronic device comprising a sealing layer formed from a sealing sheet as described in any one of [1] to

[16] above.

[0006] The effects of the invention If the present invention is adopted, a sealing sheet can be provided that can form a sealing layer with excellent water vapor intrusion barrier properties in the sealing of electronic devices and the like. Detailed Implementation

[0007] Sealing sheet The sealing sheet of the present invention has a laminated structure comprising a support and a sealing layer, characterized in that, The sealing layer consists of a first moisture-absorbing layer and a second moisture-absorbing layer. The first absorbent layer comprises the following components (A) and (B): (A) Olefin polymers, and (B) Semi-calcined hydrotalcite; and The second absorbent layer contains the following components (C) and (D): (C) Olefin polymers, and (D) Calcium oxide.

[0008] The olefin polymer (component (A)) and the semi-calcined hydrotalcite (component (B)) have similar refractive indices, therefore the first hygroscopic layer containing them is a layer with excellent transparency and also a layer that blocks water vapor intrusion. The second hygroscopic layer is a layer with excellent water vapor intrusion blocking properties due to the inclusion of calcium oxide (component (D)). In addition, the moisture brought into the first hygroscopic layer by the semi-calcined hydrotalcite (component (B)) is captured by the calcium oxide (component (D)) in the second hygroscopic layer, thus suppressing the adverse conditions caused by the brought-in moisture.

[0009] In order to capture the moisture introduced by the semi-calcined hydrotalcite (component B) in the first hygroscopic layer through the calcium oxide ((D) component) of the second hygroscopic layer, it is preferable that the first hygroscopic layer and the second hygroscopic layer are in direct contact.

[0010] The sealing sheet of the present invention has a laminated structure comprising a support body and a sealing layer, wherein the sealing layer is composed of a first moisture-absorbing layer and a second moisture-absorbing layer. The lamination order of the first and second moisture-absorbing layers is not particularly limited. The sealing sheet of the present invention may have a laminated structure comprising a support body, a first moisture-absorbing layer, and a second moisture-absorbing layer in sequence, or it may have a laminated structure comprising a support body, a second moisture-absorbing layer, and a first moisture-absorbing layer in sequence. Preferably, the sealing sheet of the present invention has a laminated structure comprising a support body, a first moisture-absorbing layer, and a second moisture-absorbing layer in sequence.

[0011] The sealing sheet of the present invention may have a protective sheet. That is, the sealing sheet of the present invention may have a laminated structure comprising a support, a sealing layer (i.e., "first moisture-absorbing layer, second moisture-absorbing layer" or "second moisture-absorbing layer, first moisture-absorbing layer"), and a protective sheet in sequence.

[0012] In the sealing sheet of the present invention, other layers (e.g., adhesive layer, release layer) may exist between the support body and the sealing layer, and between the sealing layer and the protective sheet.

[0013] From the viewpoint of achieving both sealing and tightness, the thickness of the sealing layer is preferably 3–200 μm, more preferably 3–150 μm, and even more preferably 3–100 μm. From the viewpoint of balancing water vapor intrusion barrier properties and transparency, the ratio of the thickness of the second moisture-absorbing layer to the thickness of the first moisture-absorbing layer (thickness of the second moisture-absorbing layer / thickness of the first moisture-absorbing layer) is preferably 0.05–2.0, more preferably 0.05–1.5, and even more preferably 0.05–1.0.

[0014] The thickness of the support and the protective sheet is not particularly limited, but from the viewpoint of operability of the sealing sheet, it is preferably 10 to 150 μm, and more preferably 20 to 100 μm. It should be noted that when the support and the protective sheet are laminated films, the thickness mentioned refers to the thickness of the laminated film.

[0015] The haze of the sealing layer is preferably below 60%, more preferably below 40%, and even more preferably below 20%. There is no particular limitation on the lower limit of the haze of the sealing layer; for example, the haze may be above 0%. This haze can be measured according to JIS K 7136. Specifically, the haze can be measured using the method described in the Examples section below, with glass as a reference and using D65 light.

[0016] Examples of supporting and protective sheets include polyolefins such as polyethylene, polypropylene, and polyvinyl chloride; cyclic olefin polymers; polyesters such as polyethylene terephthalate (PET) and polyethylene naphthalate; and plastic films such as polycarbonate and polyimide. Both the supporting and protective sheets can be single-layer or multilayer films.

[0017] As a support and protective sheet, a low-permeability membrane with a barrier layer, or a laminated membrane of a low-permeability membrane with a barrier layer and other membranes, can be used. Examples of barrier layers include inorganic films such as silicon dioxide vapor-deposited films, silicon nitride films, and silicon oxide films. The barrier layer can be composed of multiple layers of inorganic films (e.g., silicon dioxide vapor-deposited films). Furthermore, the barrier layer can be composed of organic and inorganic materials, or it can be a composite multilayer of organic and inorganic films.

[0018] In the protective sheet, it is preferable that the surface in contact with the sealing layer undergoes a demolding treatment. On the other hand, the support body may or may not undergo a demolding treatment. Examples of demolding treatments include those using silicone resin-based mold release agents, alkyd resin-based mold release agents, and fluoropolymer-based mold release agents.

[0019] The components constituting the first and second moisture-absorbing layers will be described below. It should be noted that, unless otherwise specified, each component may be used in isolation or in combination.

[0020] <Olefin Polymers> Component (A) in the first absorbent layer and component (C) in the second absorbent layer are both olefin polymers. The olefin polymers in the first and second absorbent layers may be the same or different. In this specification, "olefin polymer" refers to a polymer in which olefin-derived building blocks (hereinafter also abbreviated as "olefin units") are the main building blocks (i.e., the amount of olefin units is the largest among all building blocks). It should be noted that, hereinafter, "building blocks derived from butene," etc., which are olefin units, may sometimes be abbreviated as "butene units," etc.

[0021] Olefin polymers can be olefin resins (e.g., propylene-butene copolymers) or olefin rubbers (e.g., butyl rubber, i.e., isobutylene-isoprene copolymers). In this specification, "olefin resin" refers to olefin polymers that cannot be cross-linked to form rubber elastomers, and "olefin rubber" refers to olefin polymers that can be cross-linked to form rubber elastomers.

[0022] As an olefin, it is preferable to have a monoolefin having one olefinic carbon-carbon double bond and / or a diene having two olefinic carbon-carbon double bonds. Examples of monoolefins include α-olefins such as ethylene, propylene, 1-butene, isobutene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. Examples of dienes include 1,3-butadiene, isoprene, 1,3-pentadiene, and 2,3-dimethylbutadiene.

[0023] Olefin polymers can be homopolymers or copolymers. Copolymers can be random copolymers or block copolymers. Furthermore, olefin polymers can be copolymers of olefins and monomers other than olefins. Examples of olefin copolymers include ethylene-nonconjugated diene copolymers, ethylene-propylene copolymers, ethylene-propylene-nonconjugated diene copolymers, ethylene-butene copolymers, ethylene-propylene-butene copolymers, propylene-butene copolymers, propylene-butene-nonconjugated diene copolymers, isobutylene-isoprene copolymers, styrene-isobutylene copolymers, and styrene-isobutylene-styrene copolymers.

[0024] (Olefin polymers with anhydride and / or carboxyl groups) Preferably, one or both of component (A) in the first moisture-absorbing layer and component (C) in the second moisture-absorbing layer comprise an olefin polymer having an anhydride group (i.e., a carbonyloxycarbonyl group (-CO-O-CO-)) and / or a carboxyl group, and more preferably, both of them comprise said polymer. The polymer is preferably an olefin polymer having an anhydride group. It should be noted that the description and examples of "olefin" and "olefin polymer" in olefin polymers having an anhydride group and / or a carboxyl group are the same as those for olefin polymers described above.

[0025] When both component (A) in the first moisture-absorbing layer and component (C) in the second moisture-absorbing layer contain olefin polymers having anhydride groups and / or carboxyl groups, the polymers may be the same or different.

[0026] Preferably, component (A) in the first absorbent layer comprises the aforementioned olefin polymers having anhydride and / or carboxyl groups, and the olefin polymers having epoxy groups described later, which form a cross-linked structure. By forming such a cross-linked structure, a first absorbent layer with excellent strength can be obtained. It should be noted that the morphology in which the olefin polymers form the cross-linked structure is also included within the scope of this invention.

[0027] Preferably, component (C) in the second absorbent layer comprises the aforementioned olefin polymers having anhydride and / or carboxyl groups, and the olefin polymers having epoxy groups described later, which form a cross-linked structure. By forming such a cross-linked structure, a second absorbent layer with excellent strength can be obtained. It should be noted that the morphology in which the olefin polymers form the cross-linked structure is also included within the scope of this invention.

[0028] Particularly desirable is that the (C) component in the second moisture-absorbing layer comprises an olefin polymer having an anhydride group and / or a carboxyl group, and the median particle size of the (D) component (calcium oxide) in the second moisture-absorbing layer is 1–300 nm. By using the fine (D) component, the decrease in the transparency of the second moisture-absorbing layer can be suppressed. Furthermore, by using the olefin polymer having an anhydride group and / or a carboxyl group, a second moisture-absorbing layer in which the fine (D) component is well dispersed can be formed. In this regard, it is presumed that the olefin polymer having an anhydride group and / or a carboxyl group acts as a dispersant for the fine (D) component. However, the present invention is not limited to such a presumption.

[0029] When using an olefin polymer having an anhydride group as the olefin polymer, the concentration of the anhydride group in the polymer is preferably 0.05–10 mmol / g, more preferably 0.10–5 mmol / g. The concentration of the anhydride group is obtained from the acid value, which is defined as the number of mg of potassium hydroxide required to neutralize the acid present in 1 g of the polymer, according to JIS K 2501.

[0030] When using an olefin polymer having an anhydride group and / or a carboxyl group as the olefin polymer, the concentration of the carboxyl group in the polymer is preferably 0.05 to 20 mmol / g, more preferably 0.10 to 10 mmol / g. The concentration of the carboxyl group is obtained from the acid value, which is defined as the number of mg of potassium hydroxide required to neutralize the acid present in 1 g of the polymer, according to JIS K 2501.

[0031] When using an olefin polymer having an anhydride group and / or a carboxyl group as the olefin polymer, the total concentration of the anhydride group and the carboxyl group in the polymer is preferably 0.05 to 20 mmol / g, more preferably 0.10 to 10 mmol / g.

[0032] From the viewpoint of sealing performance and mechanical strength of the sealing layers (first and second moisture-absorbing layers), the number-average molecular weight of olefin polymers containing anhydride and / or carboxyl groups is preferably 1,000 to 1,000,000, and more preferably 1,000 to 750,000. It should be noted that the number-average molecular weight of each component was determined by gel permeation chromatography (GPC) (polystyrene conversion). Specifically, the number-average molecular weight determined by GPC can be measured using an "LC-9A / RID-6A" instrument manufactured by Shimadzu Corporation, using a "Shodex K-800P / K-804L / K-804L" column manufactured by Showa Denko Corporation, using toluene or similar substances as the mobile phase, at a column temperature of 40°C, and calculated using a calibration curve of standard polystyrene.

[0033] Olefin polymers having anhydride and / or carboxyl groups can be manufactured, for example, by grafting the olefin polymer with an unsaturated compound having anhydride and / or carboxyl groups (e.g., maleic anhydride) under free radical reaction conditions, or by copolymerizing an unsaturated compound having anhydride and / or carboxyl groups with α-olefins.

[0034] As olefin polymers having anhydride and / or carboxyl groups, polymers available from companies such as Toho Chemical Industry Co., Ltd. and Starlight PMC Co., Ltd. can be used. Examples of such polymers include "HV-300M" (maleic anhydride modified liquid polybutene) manufactured by Toho Chemical Industry Co., Ltd., "ER688" (maleic anhydride modified liquid polybutene) manufactured by Starlight PMC Co., Ltd., "T-YP279" (maleic anhydride modified propylene-butene random copolymer) manufactured by Starlight PMC Co., Ltd., and "T-YP312" (maleic anhydride modified propylene-butene random copolymer) manufactured by Starlight PMC Co., Ltd. PMC Corporation manufactures "ER661" (maleic anhydride-modified isobutylene-isoprene random copolymer), Starlight PMC Corporation manufactures "T-YP430" (maleic anhydride-modified ethylene-methyl methacrylate copolymer), Starlight PMC Corporation manufactures "T-YP956" (maleic anhydride-modified ethylene-propylene-butene random copolymer), and Mitsubishi Chemical Corporation manufactures "DIACARNA30M" (copolymer of maleic anhydride and α-olefin), etc.

[0035] In one embodiment of the present invention, the olefin polymer having anhydride groups and / or carboxyl groups is the following polymer: (i) Preferably, it is selected from at least one of polybutene having an anhydride group and / or a carboxyl group, isobutylene-isoprene copolymer (i.e., butyl rubber) having an anhydride group and / or a carboxyl group, propylene-butene copolymer having an anhydride group and / or a carboxyl group, ethylene-methyl methacrylate copolymer having an anhydride group and / or a carboxyl group, and ethylene-propylene-butene copolymer having an anhydride group and / or a carboxyl group; (ii) Preferably, it is selected from at least one of polybutene having an anhydride group and / or a carboxyl group, isobutene-isoprene copolymer having an anhydride group and / or a carboxyl group, and propylene-butene copolymer having an anhydride group and / or a carboxyl group. (iii) More preferably, it is selected from at least one of polybutene having an anhydride group, isobutene-isoprene copolymer having an anhydride group, and propylene-butene copolymer having an anhydride group; (iv) Especially preferred are polybutenes with anhydride groups.

[0036] When an olefinic polymer having an anhydride group and / or a carboxyl group is used to form the first moisture-absorbing layer, the content of such polymer relative to the entire first moisture-absorbing layer is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, in order to further improve the water vapor penetration barrier and strength by forming a cross-linked structure.

[0037] When using an olefin polymer having an anhydride group and / or a carboxyl group to form the second moisture-absorbing layer, the content of the polymer relative to the entire second moisture-absorbing layer is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, in order to form a cross-linked structure to further improve the water vapor penetration barrier and strength, and in order to ensure that the (D) component (calcium oxide) is well dispersed in the second moisture-absorbing layer.

[0038] (Olefin polymers with epoxy groups) Preferably, one or both of component (A) in the first moisture-absorbing layer and component (C) in the second moisture-absorbing layer contain an olefin polymer with an epoxy group, and more preferably, both of them contain an olefin polymer with an epoxy group. It should be noted that the description and examples of "olefin" and "olefin polymer" in the context of olefin polymers with epoxy groups are the same as those for olefin polymers described above.

[0039] When both the first and second moisture-absorbing layers contain olefin polymers with epoxy groups, the polymers may be the same or different.

[0040] The concentration of epoxy groups in olefin polymers containing epoxy groups is preferably 0.05–10 mmol / g, more preferably 0.10–5 mmol / g. The epoxy group concentration is determined based on the epoxy equivalent obtained according to JIS K 7236-1995.

[0041] From the perspective of improving the sealing performance and mechanical strength of the sealing layer, the number average molecular weight of olefin polymers with epoxy groups is preferably 1,000 to 1,000,000, more preferably 2,000 to 750,000, and even more preferably 2,000 to 500,000.

[0042] Olefin polymers with epoxy groups can be obtained, for example, by grafting an olefin polymer with an epoxy-containing unsaturated compound (e.g., glycidyl methacrylate, 4-hydroxybutyl acrylate glycidyl ether, allyl glycidyl ether) under free radical reaction conditions, or by copolymerizing an epoxy-containing unsaturated compound with an α-olefin.

[0043] As olefin polymers with epoxy groups, polymers available from companies such as Sumitomo Chemical Co., Ltd. and Hoshikatsu PMC Co., Ltd. can be used. Examples of such polymers include "BONDFASTBF-7M" (ethylene-glycidyl methacrylate copolymer), "BONDFAST BF-2B" (ethylene-glycidyl methacrylate-vinyl acetate copolymer), and "BF-7L" (ethylene-glycidyl methacrylate-methyl acrylate copolymer) manufactured by Sumitomo Chemical Co., Ltd.; "ER829" (glycidyl methacrylate-modified propylene-butene random copolymer), "ER850" (glycidyl methacrylate-modified butyl rubber), and "ER853" (glycidyl methacrylate-modified propylene rubber) manufactured by Hoshikatsu PMC Co., Ltd. , etc., including "ER866" (glycidyl methacrylate modified butyl rubber) manufactured by Starlight PMC Co., Ltd., "T-YP276" (glycidyl methacrylate modified propylene-butene random copolymer) manufactured by Starlight PMC Co., Ltd., "T-YP313" (glycidyl methacrylate modified propylene-butene random copolymer) manufactured by Starlight PMC Co., Ltd., and "T-YP431" (glycidyl methacrylate modified ethylene-methyl methacrylate copolymer) manufactured by Starlight PMC Co., Ltd.

[0044] Olefin polymers containing epoxy groups include the following polymers: (i) Preferably, it is selected from at least one of ethylene-glycidyl methacrylate copolymer, ethylene-glycidyl methacrylate-vinyl acetate copolymer, ethylene-glycidyl methacrylate-methyl acrylate copolymer, propylene-butene copolymer having an epoxy group, isobutylene-isoprene copolymer having an epoxy group (i.e., butyl rubber), and ethylene-methyl methacrylate copolymer having an epoxy group. (ii) Preferably, it is selected from at least one of propylene-butene copolymer having an epoxy group, isobutylene-isoprene copolymer having an epoxy group, and ethylene-methyl methacrylate copolymer having an epoxy group; (iii) Further preferably, it is selected from propylene-butene copolymers having epoxy groups and / or isobutylene-isoprene copolymers having epoxy groups; (iv) Particularly preferred are propylene-butene copolymers with epoxy groups or isobutylene-isoprene copolymers with epoxy groups.

[0045] When using an epoxy-based olefin polymer, specifically an epoxy-based propylene-butene copolymer, the amount of butene units in the copolymer is preferably 1 to 50% by mass, more preferably 2 to 45% by mass, and even more preferably 3 to 40% by mass, relative to the total amount of propylene and butene units. It should be noted that the amount of butene units is based on the propylene and butene units after removing the modified portion (e.g., the portion derived from (meth)acrylate for introducing epoxy groups).

[0046] When using an epoxy-based olefin polymer, such as an isobutylene-isoprene copolymer (i.e., butyl rubber), from the viewpoint of the moisture-absorbing layer's resistance to yellowing, the amount of isoprene units in the copolymer is preferably 0.1 to 20% by mass, more preferably 0.3 to 15% by mass, and even more preferably 0.5 to 10% by mass, relative to the total amount of isobutylene and isoprene units. It should be noted that the amount of isoprene units is based on the amount of isobutylene and isoprene units after removing the modified portion (e.g., the portion derived from (meth)acrylate for introducing epoxy groups).

[0047] When using an olefin polymer with an epoxy group to form the first moisture-absorbing layer, in order to form a robust moisture-absorbing layer, its content relative to the entire first moisture-absorbing layer is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0048] When an olefin polymer with an epoxy group is used to form the second moisture-absorbing layer, in order to form a robust moisture-absorbing layer, its content relative to the entire second moisture-absorbing layer is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0049] When using olefin polymers with epoxy groups and olefin polymers with anhydride groups and / or carboxyl groups, their amounts are preferably determined based on the ratio of their functional groups. The ratio of "amount of epoxy groups (mol) in the olefin polymer with epoxy groups" to "the total amount of anhydride groups (mol) and carboxyl groups (mol) in the olefin polymer with anhydride groups and / or carboxyl groups" is preferably 100:50 to 100:1500, more preferably 100:60 to 100:1250, even more preferably 100:70 to 100:1000, and particularly preferably 100:80 to 100:900. It should be noted that, for example, when the olefin polymer with anhydride groups and / or carboxyl groups only has anhydride groups, the "total amount of anhydride groups (mol) and carboxyl groups (mol)" refers to "the amount of anhydride groups (mol)".

[0050] (Liquid olefin polymers) Preferably, one or both of component (A) in the first absorbent layer and component (C) in the second absorbent layer contain a liquid olefin polymer, and more preferably both of them contain a liquid olefin polymer. By using a liquid olefin polymer, the absorbent layer can be endowed with good adhesion and flexibility. It should be noted that the description and examples of "olefin" and "olefin polymer" in the liquid olefin polymer are the same as those of the olefin polymer described above.

[0051] When both the first and second moisture-absorbing layers contain liquid olefin polymers, the polymers may be the same or different.

[0052] In this invention, "liquid" in "liquid olefin polymer" refers to a viscosity of 5000 Pa·s or less at 25°C. Furthermore, in this invention, "viscosity at 25°C" refers to the viscosity calculated by multiplying the dynamic viscosity at 25°C, as measured by a dynamic viscoelasticity measuring device, by the density. Examples of dynamic viscoelasticity measuring devices include, for instance, a rheometer manufactured by TA Instruments (trade name: DISCOVERYHR-2).

[0053] In this invention, liquid olefin polymers having anhydride and / or carboxyl groups are classified as olefin polymers having anhydride and / or carboxyl groups. Furthermore, in this invention, liquid olefin polymers having epoxy groups are classified as olefin polymers having epoxy groups. Therefore, "liquid olefin polymers" in this invention refers to liquid olefin polymers other than those having anhydride and / or carboxyl groups and those having epoxy groups.

[0054] From the viewpoint of good adhesion and flexibility of the moisture-absorbing layer, the viscosity of liquid olefin polymers at 25°C is preferably 5–5000 Pa·s, more preferably 10–4000 Pa·s, and even more preferably 20–3000 Pa·s.

[0055] From the viewpoint of good coatability of varnishes used to form moisture-absorbing layers, the number-average molecular weight of liquid olefin polymers is preferably 100–50,000, more preferably 200–30,000, and particularly preferably 300–20,000.

[0056] Commercially available liquid olefin polymers are acceptable. Examples of such commercially available products include ENEOS Corporation's "HV-300" (liquid polybutene), ENEOS Corporation's "HV-1900" (liquid polybutene), ENEOS Corporation's "HV-50" (liquid polybutene), ENEOS Corporation's "HV-35" (liquid polybutene), Kothari Corporation's "950MW" (liquid polybutene), Kothari Corporation's "2400MW" (liquid olefin polymer), and INEOSCO Corporation's "H -1900 (liquid polybutene), INEOSCO's "H-6000" (liquid polybutene), INEOSCO's "H-18000" (liquid polybutene), Nippon Yudo Co., Ltd.'s "200N" (liquid polybutene), Nippon Soda Co., Ltd.'s "BI-2000" (hydrogenated polybutadiene), Nippon Soda Co., Ltd.'s "BI-3000" (hydrogenated polybutadiene), Nippon Soda Co., Ltd.'s "GI-3000" (hydrogenated polybutadiene), Mitsui Chemicals Co., Ltd.'s "LUCANT" LX100 (liquid olefin polymer), Mitsui Chemicals Co., Ltd.'s "LUCANT LX400" (liquid olefin polymer), Idemitsu Showa Shell Co., Ltd.'s "Poly bd R-45HT" (butadiene liquid rubber), Idemitsu Showa Shell Co., Ltd.'s "Poly bd R-15HT" (butadiene liquid rubber), Idemitsu Showa Shell Co., Ltd.'s "Poly ip" (liquid polyisoprene), Nippon Soda Co., Ltd.'s "B-1000" (liquid polybutadiene), Nippon Soda Co., Ltd.'s "B-3000" (liquid polybutadiene), Nippon Soda Co., Ltd.'s "G-3000" (liquid polybutadiene), Kuraray Co., Ltd.'s "LIR-30" (liquid polyisoprene), Kuraray Co., Ltd.'s "LIR-390" (liquid polyisoprene), and other liquid olefin polymers. Kuraray Corporation's "LIR-290" (liquid polyisoprene), Kuraray Corporation's "LBR-302" (liquid polybutadiene), Kuraray Corporation's "LBR-305" (liquid polybutadiene), Kuraray Corporation's "LBR-361" (liquid polybutadiene), Kuraray Corporation's "L-SBR-820" (liquid styrene-butadiene random copolymer), Cray Valley's "Ricon154" (liquid butadiene), and Cray Valley's "RICON 184" (liquid styrene-butadiene random copolymer), etc.

[0057] Liquid olefin polymers are preferably liquid polybutene and / or hydrogenated polybutadiene, and more preferably liquid polybutene.

[0058] When liquid olefin polymers are used to form the first moisture-absorbing layer, from the viewpoint of good adhesion and flexibility of the moisture-absorbing layer, the content of such polymers relative to the first moisture-absorbing layer as a whole is preferably 3% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less.

[0059] When liquid olefin polymers are used to form the second moisture-absorbing layer, from the viewpoint of good adhesion and flexibility of the moisture-absorbing layer, the content of the polymer relative to the second moisture-absorbing layer as a whole is preferably 3% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less.

[0060] (Other olefin polymers) Component (A) in the first absorbent layer and component (C) in the second absorbent layer may contain a non-liquid olefin polymer (also referred to as "other olefin polymers" in this specification) that does not have any of the following groups: anhydride, carboxyl, and epoxy groups. It should be noted that the description and examples of "olefin" and "olefin polymer" in other olefin polymers are the same as those for the olefin polymers described above.

[0061] When both the first and second moisture-absorbing layers contain other olefin polymers (i.e., non-liquid olefin polymers that do not have any of the following: anhydride, carboxyl, and epoxy groups), the polymers may be the same or different.

[0062] In this invention, "non-liquid" in "non-liquid olefin polymer" refers to a viscosity exceeding 5000 Pa·s at 25°C.

[0063] The number average molecular weight of other olefin polymers is preferably 10,000 to 1,000,000, and more preferably 20,000 to 750,000.

[0064] Other olefin polymers include the following polymers: (i) Preferably, it is a propylene-butene copolymer and / or an isobutylene-isoprene copolymer (i.e., butyl rubber); (ii) It is better to be an isobutylene-isoprene copolymer.

[0065] When a propylene-butene copolymer is used as component (A4), the amount of butene units in the copolymer is preferably 1 to 50% by mass, more preferably 2 to 45% by mass, and even more preferably 3 to 40% by mass, relative to the total amount of propylene units and butene units.

[0066] When isobutylene-isoprene copolymer (i.e., butyl rubber) is used as component (A4), from the viewpoint of the moisture-absorbing layer's resistance to yellowing, the amount of isoprene units in the copolymer is preferably 0.1 to 20% by mass, more preferably 0.3 to 15% by mass, and even more preferably 0.5 to 10% by mass, relative to the total amount of isobutylene units and isoprene units.

[0067] The content of other olefin polymers relative to the first moisture-absorbing layer is preferably 0-25% by mass, more preferably 0-20% by mass, and even more preferably 0-15% by mass. The content of other olefin polymers relative to the second moisture-absorbing layer is preferably 0-25% by mass, more preferably 0-20% by mass, and even more preferably 0-15% by mass.

[0068] Semi-calcined hydrotalcite Component (B) in the first hygroscopic layer is semi-calcined hydrotalcite. Hydrotalcite can be classified into uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite.

[0069] Uncalcined hydrotalcite is made from natural hydrotalcite (Mg6Al2(OH)2). 16 Metal hydroxides with layered crystal structures, such as CO3·4H2O, are examples of metal hydroxides with layered crystal structures, for instance, those consisting of layers [Mg] forming the basic framework. 1-X Al X (OH)2] X+ and the intermediate layer [(CO3)] X / 2 ·mH2O] X- Formation. Uncalcined hydrotalcite is a concept encompassing hydrotalcite-like compounds, including synthetic hydrotalcite. Examples of hydrotalcite-like compounds include those represented by formulas (I) and (II) below.

[0070] [M 2+ 1-x M 3+ x (OH)2] x+ ·[(A n- ) x / n ·mH2O] x- (I) (where M is in the formula) 2+ Indicates Mg 2+ Zn 2+ divalent metal ions, M 3+ Indicates Al 3+ Fe 3+ Trivalent metal ions, A n- CO3 2- Cl - NO3 - (For anions with the same n-valent valence, 0 < x < 1, 0 ≤ m < 1, and n is a positive number.) In formula (I), M 2+ Mg is better 2+ M 3+ Al is better 3+ A n- CO3 is better 2- .

[0071] M 2+ x Al2(OH) 2x+6-nz (A n- ) z ·mH2O (II) (where M is in the formula) 2+ Indicates Mg 2+ Zn 2+ Isovalent metal ions, A n- CO3 2- Cl - NO3 - For anions with the same n-valent oxidation state, x is a positive number greater than 2, z is a positive number less than 2, m is a positive number, and n is a positive number. In equation (II), M 2+ Mg is better 2+ A n- CO3 is better 2- .

[0072] Semi-calcined hydrotalcite refers to a layered crystal structure of metal hydroxide obtained by calcining uncalcined hydrotalcite, resulting in a reduced or absent amount of interlayer water. If described using a compositional formula, "interlayer water" refers to "H₂O" as recorded in the compositional formula of the aforementioned uncalcined natural hydrotalcite and hydrotalcite-like compounds.

[0073] On the other hand, calcined hydrotalcite refers to a metal oxide with an amorphous structure obtained by calcining uncalcined or semi-calcined hydrotalcite, in which not only the interlayer water but also the hydroxyl groups disappear due to condensation dehydration.

[0074] Uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite can be distinguished by their saturated water absorption rate. Semi-calcined hydrotalcite has a saturated water absorption rate of 1% by mass or more but less than 20% by mass. On the other hand, uncalcined hydrotalcite has a saturated water absorption rate of less than 1% by mass, while calcined hydrotalcite has a saturated water absorption rate of 20% by mass or more.

[0075] "Saturated water absorption rate" refers to the rate of increase in mass relative to the initial mass of a 1.5g sample (e.g., semi-calcined hydrotalcite) after weighing it on a balance and measuring its initial mass. After standing for 200 hours in a small environmental test chamber (ESPEC Corporation SH-222) set at atmospheric pressure, 60°C, and 90% RH (relative humidity), it can be obtained by the following formula (i). Saturated water absorption rate (mass%) = 100 × (mass after moisture absorption - initial mass) / initial mass (i).

[0076] The saturated water absorption rate of semi-calcined hydrotalcite is preferably above 3% by mass and below 20% by mass, and more preferably above 5% by mass and below 20% by mass.

[0077] Furthermore, uncalcined hydrotalcite, semi-calcined hydrotalcite, and calcined hydrotalcite can be distinguished by the rate of decrease in thermal mass determined by thermogravimetric analysis. Semi-calcined hydrotalcite has a thermal mass decrease rate of less than 15% by mass at 280°C and a thermal mass decrease rate of more than 12% by mass at 380°C. On the other hand, uncalcined hydrotalcite has a thermal mass decrease rate of more than 15% by mass at 280°C, and calcined hydrotalcite has a thermal mass decrease rate of less than 12% by mass at 380°C.

[0078] Thermogravimetric analysis (TGA) can be performed using a Hitachi High-Tech Science TG / DTAEXSTAR 6300. Weigh 5 mg of hydrotalcite into an aluminum sample dish, leave it uncovered, and heat from 30°C to 550°C at a rate of 10°C / min under a nitrogen flow rate of 200 mL / min. The rate of decrease in thermogravimetric analysis can be calculated using the following formula (ii). Heat loss rate (mass%) = 100 × (mass before heating - mass at specified temperature) / mass before heating (ii).

[0079] Furthermore, uncalcined, semi-calcined, and calcined hydrotalcite can be distinguished by the peaks and relative intensity ratios determined using powder X-ray diffraction. For semi-calcined hydrotalcite, powder X-ray diffraction reveals peaks splitting into two near 2θ of 8–18°, or peaks with shoulders due to the synthesis of two peaks. The relative intensity ratio (low-angle diffraction intensity / high-angle diffraction intensity) of the peak or shoulder appearing on the lower angle side (= low-angle side diffraction intensity) to that of the peak or shoulder appearing on the higher angle side (= high-angle side diffraction intensity) is 0.001–1000. On the other hand, for uncalcined hydrotalcite, there is only one peak near 8–18°, or the relative intensity ratio of the peak or shoulder appearing on the lower angle side to that of the peak or shoulder appearing on the higher angle side is outside the aforementioned range. Calcined hydrotalcite does not have a characteristic peak in the 8–18° region, but has a characteristic peak at 43°. For powder X-ray diffraction measurements, a powder X-ray diffraction apparatus (Panalytical, Empyrean) is used, with the cathode CuKα... Voltage: 45V, Current: 40mA, Sampling width: 0.0260°, Scanning speed: 0.0657° / s, Diffraction angle range (2θ): 5.0131~79.9711°. Peak search can be performed using the peak search function of the software attached to the diffraction apparatus, under the following conditions: minimum significance 0.50, minimum peak tip 0.01°, maximum peak tip 1.00°, baseline width 2.00°, and the method is the minimum value of the second derivative.

[0080] The best BET specific surface area for semi-calcined hydrotalcite is 1–250 m². 2 / g, preferably 5-200m 2 / g. Their BET specific surface area can be calculated using the BET method by using a specific surface area measuring device (Macsorb HM 1210 type, manufactured by MOUNTECH Corporation) to adsorb nitrogen onto the sample surface and then using the BET multi-point method.

[0081] The particle size of semi-calcined hydrotalcite is preferably 1–1000 nm, and more preferably 10–800 nm. Their particle size is determined by laser diffraction scattering particle size distribution measurement (JIS Z 8825) using volume as the median particle size of the particle size distribution.

[0082] Semi-calcined hydrotalcite can be made from materials that have undergone surface treatment with a surface treatment agent. As a surface treatment agent, examples include higher fatty acids, alkyl silanes, and silane coupling agents, with higher fatty acids and alkyl silanes being preferred. One or more surface treatment agents can be used.

[0083] Semi-calcined hydrotalcite can be commercially available. Examples of commercially available products include "DHT-4C" and "DHT-4A-2" manufactured by Kyowa Chemical Industry Co., Ltd.

[0084] From the viewpoint of water vapor intrusion barrier performance of the sealing layer, the content of component (B) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, relative to the first moisture-absorbing layer as a whole. From the viewpoint of the adhesion of the first moisture-absorbing layer, it is preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less.

[0085] <Calcium oxide> The (D) component in the second hygroscopic layer is calcium oxide. From the viewpoint of the transparency of the second hygroscopic layer, the median particle size of the (D) component is preferably less than 300 nm, more preferably less than 250 nm, and from the viewpoint of the dispersibility of the (D) component, preferably greater than 1 nm, more preferably greater than 5 nm, and even more preferably greater than 10 nm. The median particle size of the (D) component is determined by dynamic light scattering (JIS Z 8828), and the median particle size in a volume-based particle size distribution (particle size distribution) prepared based on this determination is obtained. Dynamic light scattering is a method that calculates the particle size and particle size distribution by analyzing the fluctuations corresponding to the Brownian motion velocity using photon correlation based on the scattered light observed when particles in the dispersion medium are irradiated with a laser. Specifically, the median particle size can be measured and calculated as described in the examples.

[0086] From the viewpoint of water vapor intrusion barrier properties of the sealing layer, the content of component (D) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, relative to the second moisture-absorbing layer as a whole. From the viewpoint of the adhesion properties of the second moisture-absorbing layer, it is preferably 80% by mass or less, more preferably 75% by mass or less, and even more preferably 70% by mass or less.

[0087] When using calcium oxide with a median particle size of 300 nm or less as component (D), calcium oxide with a median particle size exceeding 300 nm can be pulverized and used, or commercially available calcium oxide with a median particle size of 300 nm or less can be used. Examples of commercially available calcium oxide with a median particle size exceeding 300 nm include "QC-X" manufactured by Inoue Lime Industry Co., Ltd., "WAC series" manufactured by Sankyo Flour Co., Ltd., and "HAL-G", "HAL-J", "HAL-F", "HAL-O", and "HAL-P" manufactured by Yoshizawa Lime Industry Co., Ltd. Examples of commercially available calcium oxide with a median particle size of 300 nm or less include "CaO Nano Powder" manufactured by Filgen.

[0088] <Other Ingredients> Both the first and second moisture-absorbing layers may contain components other than components (A) to (D) (hereinafter also referred to as "other components"), to a extent that does not impair the effects of the present invention. Examples of other components include adhesion promoters, metal complexes, antioxidants, curing accelerators, plasticizers, etc. Only one of these may be used, or two or more may be used together. Hereinafter, adhesion promoters and the like will be described in turn.

[0089] (Adhesion-enhancing agent) Adhesion-improving agents are components that impart adhesiveness to the moisture-absorbing layer. Examples of adhesion-improving agents include rosin resins, terpene resins, modified terpene resins (hydrogenated terpene resins, terpene phenol copolymer resins, aromatic modified terpene resins, etc.), petroleum resins (aliphatic petroleum resins, hydrogenated petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, copolymer petroleum resins), coumarone-indene resins, alkylphenol resins, xylene resins, etc.

[0090] Adhesion enhancers can be commercially available products. Examples of such commercially available products include, for example, the following rosin-based resins: Pine Crystal ME-H, Pine Crystal ME-D, Pine Crystal ME-G, Pine Crystal KR-85, Pine Crystal KE-311, Pine Crystal KE-359, Pine Crystal D-6011, Pine Crystal PE-590, Pine Crystal KE-604, and Pine Crystal PR-580 (all manufactured by Arakawa Chemical Industry Co., Ltd.).

[0091] Examples of terpene resins include YS RESIN PX1000, YS RESIN PX1150, YS RESIN PX1150N, YS RESIN PX1250, YS RESIN TH130, YS RESIN TR105, YS RESIN LP, and YS RESIN CP (all manufactured by Yasuhara Chemical Co., Ltd.).

[0092] Examples of hydrogenated terpene resins include the CLEARON P, CLEARON M, and CLEARON K series (all manufactured by Yasuhara Chemical Co., Ltd.).

[0093] Examples of terpene phenol copolymer resins include YS POLYSTER 2000, POLYSTER U, POLYSTER T, POLYSTER S, and Mighty Ace G (all manufactured by Yasuhara Chemical Co., Ltd.).

[0094] Examples of aromatic modified terpene resins include YS RESIN TO85, YS RESIN TO105, YS RESIN TO115, and YS RESIN TO125 (all manufactured by Yasuhara Chemical Co., Ltd.).

[0095] Examples of hydrogenated petroleum resins include Escorez 5300 and 5600 series (both manufactured by ExxonMobil), T-REZ OP501, T-REZ PR803, T-REZ HA085, T-REZ HA103, T-REZ HA105, and T-REZ HA125 (all hydrogenated dicyclopentadiene petroleum resins manufactured by ENEOS Corporation), Quintone 1325 and Quintone 1345 (both manufactured by Zeon Corporation of Japan), I-MARV S-100, I-MARV S-110, I-MARV P-100, I-MARV P-125, and I-MARV P-140 (all hydrogenated dicyclopentadiene petroleum resins manufactured by Idemitsu Kosan Co., Ltd.), and ARKON P-90, ARKON P-100, and ARKON P-140. P-115, ARKON P-125, ARKON P-140, ARKON M-90, ARKON M-100, ARKON M-115, ARKON M-135, TFS13-030 (all manufactured by Arakawa Chemical Industry Co., Ltd.), etc.

[0096] Examples of aromatic petroleum resins include ENDEX 155 (manufactured by Eastman Chemical Company), Neopolymer L-90, Neopolymer 120, Neopolymer 130, Neopolymer 140, Neopolymer 150, Neopolymer 170S, Neopolymer 160, Neopolymer E-100, Neopolymer E-130, Neopolymer M-1, Neopolymer S, Neopolymer S100, Neopolymer 120S, Neopolymer 130S, Neopolymer EP-140 (all manufactured by ENEOS Corporation), Petcoal LX, Petcoal 120, Petcoal 130, Petcoal 140 (all manufactured by Tosoh Corporation), T-REZ RB093, T-REZ RC100, T-REZ RC115, T-REZ RC093, and T-REZ... RE100 (all manufactured by ENEOS Corporation), etc.

[0097] Examples of copolymerized petroleum resins include T-REZ HB103, T-REZ HB125, T-REZ PR801, T-REZ PR802, T-REZ RD104 (all manufactured by ENEOS Corporation), Petrotack 60, Petrotack 70, Petrotack 90, Petrotack 90HS, Petrotack 90V, Petrotack 100V (all manufactured by Tosoh Corporation), and Quintone D100 (manufactured by Zeon Corporation of Japan).

[0098] From the perspective of the heat resistance of the absorbent layer, the softening point of the adhesive agent is preferably 50–200℃, more preferably 90–180℃, and even more preferably 100–170℃. It should be noted that the softening point is determined according to JIS K2207 using the ring and ball method.

[0099] When an adhesive agent is used to form the first moisture-absorbing layer, from the viewpoint of the adhesion and sealing properties of the first moisture-absorbing layer, its content relative to the entire first moisture-absorbing layer is preferably 1 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 5 to 30% by mass. When an adhesive agent is used to form the second moisture-absorbing layer, from the viewpoint of the adhesion and sealing properties of the second moisture-absorbing layer, its content relative to the entire second moisture-absorbing layer is preferably 1 to 50% by mass, more preferably 2 to 40% by mass, and even more preferably 5 to 30% by mass.

[0100] (Metal complex) To better disperse component (B) in the first hygroscopic layer, a metal complex can be formed by combining a bidentate ligand with two oxygen atoms (hereinafter referred to as "oxygen-bident ligand") and a monodentate ligand with an oxygen atom (hereinafter referred to as "oxygen-monodentate ligand") with a central metal. Furthermore, to better disperse component (D) in the second hygroscopic layer, the aforementioned metal complex can be used.

[0101] The metal complex is preferably a metal complex represented by the following formula (1) (hereinafter also referred to as "metal complex (1)").

[0102] [Chemical Formula 1]

[0103] In formula (1), M indicates a metal with a valence of divalent or higher; R1 and R3 independently represent hydrogen atom, alkyl, alkenyl, alkoxy, alkenyloxy, aryl, or aralkyl; R2 represents a hydrogen atom, alkyl, alkenyl, alkynyl, alkoxy, alkenyloxy, alkoxycarbonyl, aryl, or aralkyl; X represents a monodentate ligand; In equation (1), the solid line between the oxygen atom (O) in [] and M represents a covalent bond; In equation (1), the dashed line between the oxygen atom (O) within the brackets [] and M represents a coordinate bond; and m represents 3 or 4, and n represents an integer from 0 to 4, where m ≥ n. A single metal complex can be used, or two or more can be used together.

[0104] In the above formula (1), M is preferably a metal of Group 4 of the periodic table or a metal of Group 13 of the periodic table, and more preferably aluminum, titanium or zirconium.

[0105] In this specification, examples of halogen atoms include fluorine, chlorine, bromine, and iodine.

[0106] In this specification, the alkyl group can be either straight-chain or branched. The alkyl group (excluding the alkyl group in long-chain alkyl esters of (meth)acrylate) preferably has 1 to 20 carbon atoms, more preferably 1 to 10, and particularly preferably 1 to 6. Examples of alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, isopentyl, neopentyl, 1-ethylpropyl, hexyl, isohexyl, 1,1-dimethylbutyl, 2,2-dimethylbutyl, 3,3-dimethylbutyl, and 2-ethylbutyl. The alkyl group may optionally have a substituent. Examples of such substituents include halogen atoms, hydroxyl groups, and optionally substituent-containing amino groups.

[0107] In this specification, the alkenyl group can be either linear or branched. The alkenyl group preferably has 2 to 20 carbon atoms. Examples of alkenyl groups include vinyl (i.e., vinyl group), 1-propenyl, 2-propenyl, 2-methyl-1-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 3-methyl-2-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 4-methyl-3-pentenyl, 1-hexenyl, 3-hexenyl, 5-hexenyl, etc. The alkenyl group may optionally have substituents. Examples of substituents include halogen atoms, hydroxyl groups, and optionally substituted amino groups.

[0108] In this specification, the alkynyl group can be either straight-chain or branched. The number of carbon atoms in the alkynyl group is preferably 2 to 10, more preferably 2 to 6. Examples of alkynyl groups include ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, 2-pentynyl, 3-pentynyl, 4-pentynyl, 1-hexynyl, 2-hexynyl, 3-hexynyl, 4-hexynyl, 5-hexynyl, 4-methyl-2-pentynyl, etc. The alkynyl group may optionally have a substituent. Examples of substituents include halogen atoms, hydroxyl groups, and optionally substituent-containing amino groups.

[0109] In this specification, the aryl group preferably has 6 to 18 carbon atoms, and more preferably 6 to 14. Examples of aryl groups include phenyl, 1-naphthyl, 2-naphthyl, 1-anthrayl, 2-anthrayl, and 9-anthrayl. The aryl group may optionally have substituents. Examples of substituents include halogen atoms, hydroxyl groups, alkyl groups optionally with substituents, alkenyl groups optionally with substituents, alkynyl groups optionally with substituents, and amino groups optionally with substituents.

[0110] In this specification, the aralkyl group preferably has 7 to 16 carbon atoms. Examples of aralkyl groups include benzyl, phenethyl, naphthylmethyl, and phenylpropyl. The aralkyl group may optionally have substituents. Examples of substituents include halogen atoms, hydroxyl groups, and amino groups that may optionally have substituents.

[0111] In this specification, examples of amino groups optionally having substituents include amino groups, mono- or dialkylamino groups (e.g., methylamino, dimethylamino, ethylamino, diethylamino, propylamino, dibutylamino), mono- or dicycloalkylamino groups (e.g., cyclopropylamino, cyclohexylamino), mono- or diarylamino groups (e.g., phenylamino), mono- or diarylalkylamino groups (e.g., benzylamino, dibenzylamino), heterocyclic amino groups (e.g., pyridylamino), etc.

[0112] In this specification, the alkyl group in alkoxy (i.e., alkyloxy) is described in the same way as the alkyl group described above. Alkoxy groups may optionally have substituents. Examples of such substituents include halogen atoms, hydroxyl groups, and optionally substituents such as amino groups.

[0113] In this specification, the description of the alkenyl group in the alkenyloxy group is the same as that of the alkenyl group described above. The alkenyloxy group may optionally have a substituent. Examples of such substituents include halogen atoms, hydroxyl groups, and amino groups that may optionally have substituents.

[0114] In this specification, the alkyl group in alkoxycarbonyl (i.e., alkyloxycarbonyl) is described in the same way as the alkyl group described above. The alkoxycarbonyl group may optionally have substituents. Examples of such substituents include halogen atoms, hydroxyl groups, and optionally substituents such as amino groups.

[0115] Examples of monodentate ligands represented by X in formula (1) include, for example, alkoxide anions (RO). - (In the aforementioned formula, R represents an organic group), carboxylate anion (RCOO) - (In the aforementioned formula, R represents an organic group), oxo (O), etc.

[0116] Alkyl salt anions from RO - (In the aforementioned formula, R represents an organic group). The organic group R can be any of an aliphatic group or an aromatic group. Furthermore, the aliphatic group can be any of a saturated aliphatic group or an unsaturated aliphatic group. The organic group R preferably has 1 to 20 carbon atoms, more preferably 6 to 18, and particularly preferably 8 to 14. As an alkoxide anion (RO... - Examples of such salts include methanol salts, ethanol salts, propanol salts, isopropanol salts, butanol salts, isobutanol salts, sec-butanol salts, tert-butanol salts, pentanol salts, hexanol salts, phenol salts, and 4-methylphenol salts.

[0117] The carboxylate anion is produced by RCOO - (In the aforementioned formula, R represents an organic group). The organic group R can be any of an aliphatic group or an aromatic group. Furthermore, the aliphatic group can be any of a saturated aliphatic group or an unsaturated aliphatic group. The organic group R preferably has 1 to 20 carbon atoms, more preferably 6 to 18, and particularly preferably 8 to 14. As a carboxylate anion (RCOO) - Examples of carboxylic acid anions include those corresponding to carboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, octylic acid, nonanoic acid, decanoic acid, dodecanoic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, and benzoic acid.

[0118] In formula (1), the brackets [] represent polydentate ligands. Examples of polydentate ligands include: acetylacetone, 3-methyl-2,4-pentanedione, acetoacetaldehyde, 2,4-hexanedione, 2,4-heptanedione, 5-methyl-2,4-hexanedione, 5,5-dimethyl-2,4-hexanedione, benzoylacetone, benzoylacetophenone, salicylaldehyde, 1,1,1-trifluoroacetylacetone, 1,1,1,5,5,5-hexafluoroacetylacetone, 3-methoxy-2,4-pentanedione, 3-cyano-2,4-pentanedione, 3-nitro-2,4-pentanedione, 3-chloro-2,4-pentanedione, acetoacetic acid, methyl acetoacetate, ethyl acetoacetate, propyl acetoacetate, salicylic acid, methyl salicylate, malonic acid, dimethyl malonate, diethyl malonate, etc. When coordinated with the central metal, the polydentate ligand is formed into a structure obtained by removing one or more protons from it.

[0119] Specific examples of metal complexes (1) with M being aluminum include: aluminum diisopropoxide mono-sec-butoxide, aluminum tri-sec-butoxide, aluminum triisopropylate, aluminum triethanolate, aluminum triacetylacetonate, aluminum bis(ethylacetoacetate)mono(acetylacetonate), aluminum tris(ethylacetoacetate), and aluminum octadecenylacetate diisopropylate. diisopropylate, ethylaluminum diisopropyl acetoacetate, ethylaluminum di-n-butyl acetoacetate, propylaluminum diisopropyl acetoacetate, n-butylaluminum diisopropyl acetoacetate, tri(ethylacetoacetate)aluminum, diethylacetate ethanol-2,4-pentanedione aluminum (Aluminum mono(acetylacetonate)bis(ethylacetoacetate)), tri(acetylacetonate)aluminum.

[0120] Specific examples of titanium metal complexes (1) include: tetraisopropyl titanate, tetra-n-butyl titanate, tetraoctyl titanate, tetra-tert-butyl titanate, tetrastearyl titanate, titanium tetraacetylacetonate, titanium octylene glycol titanate (also known as bis(2-ethylhexyloxy)bis(2-ethyl-3-oxohexyloxy)titanium(IV)), diisopropyl bis(ethyl acetoacetate)titanium, titanium allyl acetoacetate triisopropoxide, and titanium di-n-butoxide. bis(2,4-pentanedionate), diisopropoxybis(tetramethylheptanedionate)titanium, diisopropyl bis(acetoacetate)titanium, titanium(IV)tetra(methylphenoxide), bis(2,4-pentanedione)titanium oxide, monoisopropyl triisostearate titanate, diisopropyl diisostearate titanate.

[0121] Specific examples of metal complexes (1) with M being zirconium include: zirconium tetra-n-propoxide (zirconium tetra-n-propoxide), zirconium tetra-n-butoxy, zirconium tetraacetylacetone, zirconium triisopropoxyacetoacetate, zirconium di-n-butoxybis(2,4-pentanedione), zirconium diisopropoxybis(2,4-pentanedione), zirconium diisopropoxybis(tetramethylheptanedane), zirconium diisopropoxybis(ethoxyacetate), zirconium butoxide(acetylacetate)bis(ethoxyacetate), zirconium tributoxymonoacetylacetone, zirconium octanoate, zirconium stearate, zirconium monooctanoate tri-n-butyl, zirconium monostearate.

[0122] When a metal complex is used to form the first moisture-absorbing layer, from the viewpoint of the dispersibility of component (B) in the first moisture-absorbing layer, its content relative to the entire first moisture-absorbing layer is preferably 0.01 to 3% by mass, more preferably 0.05 to 2.5% by mass, and even more preferably 0.10 to 2% by mass. When a metal complex is used to form the second moisture-absorbing layer, from the viewpoint of the dispersibility of component (D) in the second moisture-absorbing layer, its content relative to the entire second moisture-absorbing layer is preferably 0.01 to 3% by mass, more preferably 0.05 to 2.5% by mass, and even more preferably 0.10 to 2% by mass.

[0123] (Antioxidants) In this invention, there is no particular limitation on the antioxidant, and known antioxidants can be used. When an antioxidant is used to form the first moisture-absorbing layer, its content relative to the entire first moisture-absorbing layer is preferably 0.01 to 5% by mass, more preferably 0.05 to 2.5% by mass, and even more preferably 0.10 to 2% by mass. When an antioxidant is used to form the second moisture-absorbing layer, its content relative to the entire second moisture-absorbing layer is preferably 0.01 to 5% by mass, more preferably 0.05 to 2.5% by mass, and even more preferably 0.10 to 2% by mass.

[0124] (Curing accelerator) In this invention, a curing accelerator can be used to promote the crosslinking reaction between olefin polymers having anhydride and / or carboxyl groups and olefin polymers having epoxy groups. Examples of curing accelerators include imidazole compounds, tertiary / quaternary amine compounds, dimethylurea compounds, and organophosphorus compounds.

[0125] Examples of imidazole compounds include 1H-imidazolium, 2-methylimidazolium, 2-phenyl-4-methylimidazolium, 2-ethyl-4-methylimidazolium, 1-cyanoethyl-2-ethyl-4-methylimidazolium, 2-undecylimidazolium, 1-cyanoethyl-2-undecylimidazolium, 1-cyanoethyl-2-undecylimidazolium trimellitate, 2-phenyl-4,5-bis(hydroxymethyl)imidazolium, 1-benzyl-2-methylimidazolium, 1-benzyl-2-phenylimidazolium, 2-phenylimidazolium, 2-dodecylimidazolium, 2-heptadecanylimidazolium, 1,2-dimethylimidazolium, 2-phenyl-4-methyl-5-hydroxymethylimidazolium, etc. Specific examples of imidazole compounds include Curezol 2MZ, 2P4MZ, 2E4MZ, 2E4MZ-CN, C11Z, C11Z-CN, C11Z-CNS, C11Z-A, 2PHZ, 1B2MZ, 1B2PZ, 2PZ, C17Z, 1.2DMZ, 2P4MHZ-PW, 2MZ-A, and 2MA-OK (all manufactured by Shikoku Chemical Industry Co., Ltd.).

[0126] As tertiary / quaternary amine compounds, there are no particular limitations, but examples include: quaternary ammonium salts such as tetramethylammonium bromide, tetrabutylammonium bromide, and triethylmethylammonium 2-ethylhexanoate; diazabicyclic compounds such as DBU (1,8-diazabicyclo[5.4.0]undecene-7), DBN (1,5-diazabicyclo[4.3.0]nonene-5), DBU-phenol salts, DBU-octanoate, DBU-p-toluenesulfonate, DBU-formate, and DBU-linear phenolic resin salts; tertiary amines or their salts such as benzyl dimethylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris(dimethylaminomethyl)phenol (TAP); and dimethylurea compounds such as aromatic dimethylurea and aliphatic dimethylurea.

[0127] Examples of dimethylurea compounds include aromatic dimethylureas such as DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea) and U-CAT3512T (manufactured by San-Apro); and aliphatic dimethylureas such as U-CAT3503N (manufactured by San-Apro). From a curing perspective, aromatic dimethylureas are preferred.

[0128] Examples of organophosphorus compounds include triphenylphosphine, tetraphenylphosphine tetratolylborate, tetraphenylphosphine tetraphenylborate, tri-tert-butylphosphine tetraphenylborate, (4-methylphenyl)triphenylphosphine thiocyanate, tetraphenylphosphine thiocyanate, butyltriphenylphosphine thiocyanate, and triphenylphosphine triphenylborane. Specific examples of organophosphorus compounds include TPP, TPP-MK, TPP-K, TTPuP-K, TPP-SCN, and TPP-S (all manufactured by Hokuko Chemical Industry Co., Ltd.).

[0129] When a curing accelerator is used to form the first moisture-absorbing layer, its content relative to the entire first moisture-absorbing layer is preferably 0.001 to 5% by mass, more preferably 0.001 to 2.5% by mass, and even more preferably 0.001 to 1% by mass. When a curing accelerator is used to form the second moisture-absorbing layer, its content relative to the entire second moisture-absorbing layer is preferably 0.001 to 5% by mass, more preferably 0.001 to 2.5% by mass, and even more preferably 0.001 to 1% by mass.

[0130] (Plasticizer) The moisture-absorbing layer may further contain plasticizers. Examples of plasticizers include paraffinic processed oils, naphthenic processed oils, liquid paraffin, mineral oils such as petrolatum, and vegetable oils such as castor oil, cottonseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, and olive oil.

[0131] <Manufacturing Method of Sealing Sheets> The sealing sheet of the present invention can be manufactured, for example, as follows: the above-mentioned components and an organic solvent are mixed to prepare a varnish (hereinafter also referred to as "first varnish") for forming a first moisture-absorbing layer and a varnish (hereinafter also referred to as "second varnish") for forming a second moisture-absorbing layer; one of the obtained first varnish and second varnish is applied to a support and dried to form one of the first moisture-absorbing layer or the second moisture-absorbing layer; the other of the first varnish and second varnish is applied to the moisture-absorbing layer and dried to form the other of the first moisture-absorbing layer or the second moisture-absorbing layer.

[0132] A sealing sheet having a laminated structure comprising a support, a sealing layer, and a protective sheet in sequence can be manufactured, for example, as follows: one of a first varnish and a second varnish is applied to one of the support and the protective sheet and dried to form one of a first moisture-absorbing layer or a second moisture-absorbing layer; the other of the first varnish and the second varnish is applied to the moisture-absorbing layer and dried to form the other of a first moisture-absorbing layer or a second moisture-absorbing layer; and the other of the support and the protective sheet is laminated on the formed sealing layer ("first moisture-absorbing layer / second moisture-absorbing layer" or "second moisture-absorbing layer / first moisture-absorbing layer").

[0133] When using a first varnish and a second varnish with appropriate viscosity, a coating film is formed by applying one of the first varnish and the second varnish to a support or protective sheet, and the other of the first varnish and the second varnish is applied to the formed coating film to form a two-layer coating film. The two layers are dried together, thereby forming a sealing layer ("first moisture-absorbing layer / second moisture-absorbing layer" or "second moisture-absorbing layer / first moisture-absorbing layer").

[0134] Examples of organic solvents that can be used in the manufacture of varnishes include: ketones such as acetone, methyl ethyl ketone, and cyclohexanone; acetates such as ethyl acetate, butyl acetate, cellosol acetate, propylene glycol monomethyl ether acetate, and carbitol acetate; cellosols such as cellulose solvents; carbitols such as butyl carbitol; aromatics such as toluene and xylene; and amides such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone. Commercially available organic solvents can be used, such as "Swasol" manufactured by Maruzen Petrochemical Co., Ltd., and "Ipzole" manufactured by Idemitsu Kosan Co., Ltd. Only one organic solvent can be used, or two or more can be used in combination.

[0135] The drying of the coating film formed by applying varnish is preferably carried out by heating the coating film. The heating temperature of the coating film is preferably 50–200°C, more preferably 80–150°C, and the heating time is preferably 1–60 minutes, more preferably 5–30 minutes. The heating of the coating film can be carried out under normal pressure or under reduced pressure.

[0136] The coating obtained by removing the organic solvent can be further aged by heating. The preferred heating temperature is 80–200°C, more preferably 100–150°C, and the preferred heating time is 10–240 minutes, more preferably 30–180 minutes. This heating can be carried out under normal pressure or under reduced pressure.

[0137] Hereinafter, a preferred manufacturing method for the sealing sheet of the present invention having a second absorbent layer comprising fine (D) components with a median particle size of 1 to 300 nm will be described. However, the sheet may also be manufactured by methods other than those described below.

[0138] The varnish used to form the second moisture-absorbing layer is preferably manufactured by a process of pulverizing a mixture comprising an olefin polymer having an anhydride group and / or a carboxyl group, calcium oxide with a median particle size greater than 300 nm, and an organic solvent. While it is also possible to manufacture a varnish by mixing calcium oxide with a median particle size of less than 300 nm with other components, such simple mixing makes it difficult to achieve good dispersion of fine calcium oxide in the varnish compared to the process described above. Furthermore, the large surface area of ​​fine calcium oxide results in increased hygroscopicity. To avoid such hygroscopicity, the workability of fine calcium oxide in varnish manufacturing is worse than that of calcium oxide of normal size. Hereinafter, a preferred method for manufacturing the sealing sheet of the present invention having a second moisture-absorbing layer comprising fine (D) components will be described.

[0139] Preferably, the mixture for pulverization is prepared by first mixing calcium oxide with a median particle size exceeding 300 nm, an olefin polymer having anhydride and / or carboxyl groups, and an organic solvent. The calcium oxide content is preferably 3-75% by mass, more preferably 5-70% by mass, relative to the total mixture for pulverization. The olefin polymer having anhydride and / or carboxyl groups is preferably 3-40% by mass, more preferably 5-35% by mass, relative to the total mixture for pulverization. The organic solvent content is preferably 20-70% by mass, more preferably 30-60% by mass, relative to the total mixture for pulverization.

[0140] The organic solvents described above can be used as the organic solvents for the mixture used in the pulverizing process. Only one organic solvent may be used, or two or more may be used in combination.

[0141] Any components can be added to the mixture used for pulverization, such as liquid olefin polymers and adhesion promoters. There are no particular restrictions on the order of addition of the components; they can be added sequentially or simultaneously.

[0142] The grinding process can be carried out using a known grinder. Through grinding, calcium oxide is pulverized and dispersed in the mixture. Examples of known grinders include, for example, a wet bead mill. Examples of bead materials include, for example, zirconium oxide, alumina, glass, and steel. The bead diameter is, for example, approximately 0.03 to 5 mm. The rotational speed of the bead mill's shaft is, for example, approximately 10 to 10,000 rpm. The flow rate of the mixture for grinding into the grinding chamber of the bead mill is, for example, approximately 0.1 to 10,000 kg / hour. In wet grinding using a bead mill, to suppress the temperature rise of the mixture during grinding, it is preferable to perform cooling with cooling water simultaneously. The temperature of the cooling water is, for example, approximately 0 to 40°C.

[0143] Any components may be further added and mixed into the pulverized mixture. For example, epoxy-based olefin polymers, liquid olefin polymers, adhesion promoters, etc., may be added to and mixed into the pulverized mixture. There is no particular limitation on the order of addition of the components; the components may be added sequentially or simultaneously. When the varnish contains epoxy-based olefin polymers, it is preferable to mix the pulverized mixture with the epoxy-based olefin polymers to prevent cross-linking reactions due to heat during pulverization. In addition to using a varnish for forming a second moisture-absorbing layer containing fine (D) components, the sealing sheet of the present invention having a second moisture-absorbing layer containing fine (D) components can be manufactured by the same method as described above.

[0144] <Electronic Devices> The present invention also provides an electronic device comprising a sealing layer formed from the sealing sheet of the present invention. Examples of electronic devices include, for example, organic EL devices, solar cells, sensor devices, and touch panels having a conductive substrate. Preferably, the electronic device is an organic EL device or a solar cell, which are less resistant to moisture. Example

[0145] The present invention will be described in more detail below with examples. The present invention is not limited to the following examples and may be implemented with appropriate modifications within the scope of the context, all of which are included within the technical scope of the present invention. It should be noted that unless otherwise specified, "parts" and "%" in the amounts of components and copolymer units refer to "parts by mass" and "% by mass," respectively.

[0146] <Ingredients> The components used in the manufacturing example are shown below; (1) Olefin polymers having anhydride groups and / or carboxyl groups “HV-300M” (manufactured by Toho Chemical Industry Co., Ltd., maleic anhydride modified liquid polybutene, anhydride concentration: 0.77 mmol / g, number average molecular weight: 2100).

[0147] (2) Olefin polymers with epoxy groups “ER829” (manufactured by Starlight PMC Co., Ltd., glycidyl methacrylate modified propylene-butene random copolymer, propylene unit / butene unit: 71% / 29%, epoxy group concentration: 0.64 mmol / g, number average molecular weight: 168000) “ER866” (manufactured by Starlight PMC Co., Ltd., glycidyl methacrylate modified butyl rubber, epoxy group concentration: 1.63 mmol / g, number average molecular weight: 113000, isobutylene unit / isoprene unit: 98.9% / 1.1%).

[0148] (3) Liquid olefin polymers “HV-1900” (manufactured by ENEOS Corporation, liquid polybutene, number average molecular weight: 2900, viscosity at 25°C: 460 Pa·s).

[0149] (4) Other olefin polymers “BUTYL065” (manufactured by JSR Corporation, butyl rubber, isobutylene unit / isoprene unit: 98.7% / 1.3%).

[0150] (5) Packing (5-1) Semi-calcined hydrotalcite "DHT-4C" (manufactured by Kyowa Chemical Industry Co., Ltd., semi-calcined hydrotalcite, median particle size: 400nm, BET specific surface area: 15m²) 2 / g) (5-2) Calcium oxide Calcium oxide (manufactured by Yoshizawa Lime Industry Co., Ltd., median particle size: 2.1 μm) (5-3) Plate-shaped packing “PDM-5B” (manufactured by TOPY Industrial Co., Ltd., synthetic fluorophlogopite, median particle size: 6.0 μm, average aspect ratio: 40).

[0151] (6) Adhesion-enhancing agents "ARKON P-125" (manufactured by Arakawa Chemical Industry Co., Ltd., hydrogenated petroleum resin, softening point: 125°C).

[0152] (7) Metal complexes "PLENACT Al-M" (manufactured by Ajinomoto Fine-Techno Co., Ltd., octadecenyl aluminum diisopropyl acetoacetate).

[0153] (8) Antioxidants "Irganox 1010" (manufactured by BASF, a hindered phenolic antioxidant).

[0154] (9) Curing accelerator 2,4,6-Tris(dimethylaminomethyl)phenol (manufactured by KAYAKUNOURYON Co., Ltd., hereinafter referred to as "TAP").

[0155] <Manufacturing Example 1> Prepare the varnishes according to the proportions shown in Tables 1-1 and 1-2 below, following the steps outlined below. It should be noted that the amounts (parts) of each component listed in Tables 1-1 and 1-2 represent the amount of non-volatile components in the varnish. Furthermore, the median particle size of the calcium oxide contained in the varnish is also listed in Tables 1-1 and 1-2.

[0156] Specifically, a mixture was obtained by mixing maleic anhydride-modified liquid polybutene (Toho Chemical Industry Co., Ltd. “HV-300M”), liquid polybutene (ENEOS Co., Ltd. “HV-1900”), and semi-calcined hydrotalcite (Kyowa Chemical Industry Co., Ltd. “DHT-4C”) in a Swasol solution (non-volatile component: 60%) of an adhesion promoter (ARKON P-125) using a three-roll mill. To the obtained mixture, a Swasol solution (non-volatile component: 15%) of glycidyl methacrylate-modified propylene-butene random copolymer ("ER829" manufactured by Starlight PMC Co., Ltd.), a hindered phenolic antioxidant ("Irganox 1010" manufactured by BASF), a curing accelerator (TAP, manufactured by KAYAKUNOURYON Co., Ltd.) and toluene were added, and the mixture was mixed using a high-speed rotary mixer to obtain a varnish.

[0157] <Manufacturing Examples 2-4> Except for changing the types and amounts of the ingredients used as shown in Table 1-1, the varnish was obtained by the same method as in Manufacturing Example 1.

[0158] <Manufacturing Example 5> To a Swasol solution (non-volatile component: 60%) containing an adhesion promoter (ARKON P-125 manufactured by Arakawa Chemical Industry Co., Ltd.), maleic anhydride-modified liquid polybutene (HV-300M manufactured by Toho Chemical Industry Co., Ltd.), liquid polybutene (HV-1900 manufactured by ENEOS Co., Ltd.), calcium oxide (Yoshizawa Lime Industry Co., Ltd.), and toluene were added to obtain a mixture for pulverization (the content of organic solvent relative to the total content of the mixture (i.e., the total content of Swasol and toluene): 24%, the content of maleic anhydride-modified liquid polybutene: 10%, the content of calcium oxide: 48%, the content of adhesion promoter: 7%, and the content of liquid polybutene: 11%).

[0159] The mixture for pulverization is added to a wet bead mill (LABSTAR Mini "LMZ015" manufactured by Ashizawa Finetech Co., Ltd.), and beads (bead diameter: 0.1 mm) are filled to about 60% of the effective volume of the pulverization chamber. Pulverization is performed to obtain a pulverized mixture in which calcium oxide is pulverized and dispersed.

[0160] A small amount of the pulverized mixture was taken and diluted 100 times with toluene to prepare a test sample. The median particle size of calcium oxide was determined and calculated using a MICROTRAC nanoparticle size analyzer, the "NANOTRAC WAVE," via dynamic light scattering. The result showed that the median particle size of calcium oxide was 185 nm.

[0161] A hindered phenolic antioxidant (BASF's "Irganox 1010") and a curing accelerator (TAP, KAYAKU NOURYON Co., Ltd.) are added to the pulverized mixture, and the mixture is mixed with a high-speed rotary mixer to obtain a varnish.

[0162] <Manufacturing Example 6> Except that the amount of calcium oxide used was changed from 300 parts to 120 parts, the varnish was obtained by the same method as in manufacturing example 5.

[0163] <Manufacturing Example 7> Except for changing the bead diameter used in the wet bead mill from 0.1 mm to 0.2 mm, the varnish was obtained by the same method as in Manufacturing Example 5. It should be noted that, in the same manner as in Manufacturing Example 5, the median particle size of calcium oxide in the mixture after pulverization in the Manufacturing Example was measured, and the result was that the median particle size was 246 nm.

[0164] <Manufacturing Example 8> Except that 60 parts of glycidyl methacrylate modified butyl rubber (manufactured by Starlight PMC Co., Ltd., "ER866") were used instead of 60 parts of glycidyl methacrylate modified propylene-butene random copolymer (manufactured by Starlight PMC Co., Ltd., "ER829"), the varnish was obtained by the same method as in Manufacturing Example 1.

[0165] <Manufacturing Examples 9 and 10> Except for changing the types and amounts of the ingredients used as shown in Tables 1-2, the varnish was obtained by the same method as in Manufacturing Example 5.

[0166] The varnishes of Manufacturing Examples 1, 2 and 8 are varnishes used to form a first hygroscopic layer containing component (B) (semi-calcined hydrotalcite), the varnishes of Manufacturing Examples 5-7, 9 and 10 are varnishes used to form a second hygroscopic layer containing component (D) (calcium oxide), and the varnishes of Manufacturing Examples 3 and 4 are varnishes used to form other layers that do not contain either component (B) or component (D).

[0167] <Example 1> A polyethylene terephthalate film (SP4020, manufactured by TOYO CLOTH CO.,LTD., PET film thickness: 50μm), treated on one side with a silicone-based release agent, and a low-moisture-permeable polyethylene terephthalate film (TECHBARRIER HX, manufactured by Mitsubishi Chemical Corporation, PET film thickness: 12μm) were laminated together with the untreated side of SP4020 in contact with TECHBARRIER HX to create a laminated film, which was used as a support and protective sheet for sealing sheets. Hereinafter, the "silicone-treated side of the laminated film" will be referred to as the "release-treated side".

[0168] A coating film was formed by uniformly applying the varnish obtained in Manufacturing Example 5 to the demolded surface of the first laminated film (protective sheet) using a die-casting machine, with a dried film thickness (i.e., the thickness of the moisture-absorbing layer) of 10 μm. A two-layer coating film was then formed by applying the varnish obtained in Manufacturing Example 1 to the formed coating film with a dried film thickness (i.e., the thickness of the moisture-absorbing layer) of 40 μm. These two layers were then heated at 140°C for 30 minutes to form a sealing layer (a two-layer moisture-absorbing layer). A cross-section of the resulting sealing layer was observed, confirming the formation of two moisture-absorbing layers. Hereinafter, the moisture-absorbing layer formed on the protective sheet will be referred to as the "moisture-absorbing layer on the component side," and the moisture-absorbing layer formed on the component side will be referred to as the "moisture-absorbing layer on the support side."

[0169] A second laminated film (support) is stacked on the moisture-absorbing layer formed on the support side, and heated at 130°C for 60 minutes to obtain a sealing sheet with a laminated structure of "moisture-absorbing layer on the protective sheet / component side / moisture-absorbing layer on the support side / support". The moisture-absorbing layer on the component side and the moisture-absorbing layer on the support side constitute the sealing layer of the sealing sheet.

[0170] <Examples 2-9> Except for changing the type of varnish used, the thickness of the moisture-absorbing layer on the component side, and the thickness of the moisture-absorbing layer on the support side as shown in Table 2-1 or Table 2-2, the same operation as in Example 1 is performed to obtain a sealing sheet having a laminated structure of "protective sheet / moisture-absorbing layer on the component side / moisture-absorbing layer on the support side / support".

[0171] <Comparative Example 1> The varnish obtained in Manufacturing Example 1 is uniformly coated on the demolding surface of the first laminated film (protective sheet) using an orifice-type coating machine at a dried film thickness (i.e., the thickness of the moisture-absorbing layer) of 50 μm. The film is then heated at 140°C for 30 minutes to form a moisture-absorbing layer on the component side.

[0172] A second laminated film (support) is stacked on the moisture-absorbing layer formed on the element side, and heated at 130°C for 60 minutes to obtain a sealing sheet with a laminated structure of "protective sheet / moisture-absorbing layer on the element side / support".

[0173] <Comparison of Examples 2 and 3> Except for changing the type of varnish used, the thickness of the layer on the component side, and the thickness of the moisture-absorbing layer on the support side as shown in Tables 2-3, the operation was carried out in the same manner as in Example 1 to obtain a sealing sheet having a laminated structure of "protective sheet / layer on the component side / moisture-absorbing layer on the support side / support". It should be noted that in Comparative Examples 2 and 3, the varnish of Manufacturing Example 3 or 4, which does not contain either component (B) (semi-calcined hydrotalcite) or component (D) (calcium oxide), was used to form the layer on the component side.

[0174] The moisture-absorbing layer formed by the varnish of Manufacturing Examples 1, 2 or 10 is a first moisture-absorbing layer containing component (B) (semi-calcined hydrotalcite), the moisture-absorbing layer formed by the varnish of Manufacturing Examples 5 to 9, 11 or 12 is a second moisture-absorbing layer containing component (D) (calcium oxide), and the layer formed by the varnish of Manufacturing Examples 3 or 4 is another layer that does not contain either component (B) or component (D).

[0175] Regarding the sealing layer of the sealing sheet obtained in the embodiments and comparative examples, the water vapor intrusion barrier and transparency were evaluated by the following method.

[0176] <Evaluation Methods for Water Vapor Intrusion Barrier> As a support, a composite film consisting of aluminum foil and polyethylene terephthalate film ("AL1N30 with PET" manufactured by Tokai Toyo Aluminum Sales Co., Ltd. (aluminum foil thickness: 30μm, PET film thickness: 25μm)) is prepared.

[0177] Except for using the composite film as a support, the same procedures as in the embodiments and comparative examples were followed to obtain test sheets having a laminated structure of "protective sheet (laminated film) / moisture-absorbing layer on the element side / moisture-absorbing layer on the support side / support (composite film)" or "protective sheet (laminated film) / moisture-absorbing layer on the element side / support (composite film)".

[0178] Prepare a 50mm x 50mm square glass plate made of alkali-free glass. Wash the glass plate with boiling isopropanol for 5 minutes and dry it at 150°C for at least 30 minutes.

[0179] On one side of the dried glass plate, calcium is deposited by vapor deposition using a mask covering a peripheral area 0 mm to 2 mm from the end of the glass plate. This forms a calcium film (99.8% purity) with a thickness of 200 nm in the central portion of one side of the glass plate, excluding the peripheral area 0 mm to 2 mm from the end of the glass plate.

[0180] In a nitrogen atmosphere, the moisture-absorbing layer on the element side of the aforementioned test sheet was bonded to the calcium film side of the glass plate using a thermal laminator (FUJIPLA Corporation "Lamipacker DAiSY A4 (LPD2325)") to obtain a laminate. This laminate was used as an evaluation sample.

[0181] Generally, calcium becomes transparent when it comes into contact with water to form calcium oxide. Furthermore, in the evaluation sample, the glass plate and aluminum foil have sufficiently high water vapor intrusion barrier properties, so moisture can usually move through the sealing layer ends in the in-plane direction (perpendicular to the thickness direction) to reach the calcium film. If moisture intrudes into the evaluation sample, the calcium film gradually oxidizes from the ends and becomes transparent, so shrinkage of the calcium film can be observed. Therefore, moisture intrusion into the evaluation sample can be evaluated by measuring the sealing distance (mm) from the end of the evaluation sample to the calcium film. Therefore, evaluation samples containing calcium films can be used as models for electronic devices.

[0182] First, the sealing distance X2 (mm) from the end of the self-evaluation sample to the end of the calcium film was measured using a microscope (Mitutoyo Co., Ltd. "Measuring Microscope MF-U").

[0183] Next, the evaluation sample was placed in a constant temperature and humidity bath set at 85°C and 85% RH. The evaluation sample was removed from the bath when the sealing distance X1 (mm) between the end of the evaluation sample placed in the bath and the end of the calcium film increased by 0.1 mm compared to the initial sealing distance X2. The reduction start time t [hours] was calculated as the time from when the evaluation sample was placed in the bath to when it was removed. This reduction start time t is equivalent to the time T from when the evaluation sample was placed in the bath. P1 The time T from the point where the sealing distance X1 [mm] between the end of the evaluation sample stored in the constant temperature and humidity bath and the end of the calcium film reaches "X2 + 0.1 mm" is taken. P2 The time up to that point.

[0184] Substituting the sealing distance X1 and the reduced start time t into the Fick diffusion equation (1), the constant K, which serves as the barrier parameter for water vapor intrusion, is calculated.

[0185] [Mathematical Expression 1]

[0186] Using the obtained constant K, the water vapor intrusion barrier properties of the sealing layer were evaluated according to the following criteria. A smaller value of constant K indicates higher water vapor intrusion barrier properties. It should be noted that "hr" below refers to "hours". The results are recorded in Tables 2-1 to 2-3 below. It should be noted that "(cm / hr ^ 0.5)" in Tables 2-1 to 2-3 means "(cm / hr ^ 0.5)". 0.5 )”; (Standards for water vapor intrusion barrier properties) 〇 (Good): Constant K is less than 0.025 cm / hr 0.5 × (Defect): Constant K is 0.025cm / hr 0.5 above.

[0187] <Methods for evaluating transparency> The sealing sheets prepared in the examples and comparative examples were cut into lengths of 70 mm and widths of 25 mm. A protective sheet was peeled off from the cut sealing sheets. The sealing sheets with the sealing layer / support laminate structure were then laminated onto a glass plate (Matsunami Glass Industry Co., Ltd., "White Glass Slide S1112 Edge Grinding No. 2", length: 76 mm, width: 26 mm, and thickness: 1.2 mm) using a batch vacuum laminator (Nichigo-Morton Co., Ltd.) to obtain an evaluation sample with a glass / sealing layer / support laminate structure. The lamination conditions were: temperature 80°C, decompression time 30 seconds, followed by pressure application at 0.3 MPa for 30 seconds.

[0188] The haze (%) of the samples was measured according to JIS K 7136. Specifically, after peeling off the support layer of the evaluation samples with a glass / sealing layer / support structure, the haze (%) of the evaluation samples after the support layer was peeled off was measured using a Suga Testing Machine Co., Ltd. HZ-V3 haze meter (halogen lamp), with the glass as a reference, and under D65 light. The transparency was evaluated according to the following criteria. The results are shown in Tables 2-1 to 2-3 below; (Standards of transparency) ○ (Good): Haze level below 30% △ (Pass): Haze level is above 30% and below 60%. × (Poor): Haze is above 60%.

[0189] [Table 1-1]

[0190] [Table 1-2]

[0191] [Table 2-1] (Postscript) The moisture-absorbing layer formed by the varnish of Manufacturing Examples 1, 2, or 8 is the first moisture-absorbing layer. The moisture-absorbing layer formed by the varnish of manufacturing examples 5-7, 9 or 10 is the second moisture-absorbing layer.

[0192] [Table 2-2] (Postscript) The moisture-absorbing layer formed by the varnish of Manufacturing Example 1 is the first moisture-absorbing layer. The moisture-absorbing layer formed by the varnish of Manufacturing Example 5 is the second moisture-absorbing layer.

[0193] [Table 2-3] (Postscript) The moisture-absorbing layer formed by the varnish of Manufacturing Example 1 is the first moisture-absorbing layer. The moisture-absorbing layer formed by the varnish in manufacturing example 3 or 4 is another layer.

[0194] The sealing layers of the sealing sheets of Examples 1 to 9, which satisfy the requirements of the present invention, have superior water vapor intrusion barrier properties compared with the sealing layers of the sealing sheets of Comparative Examples 1 to 3, which do not satisfy the requirements of the present invention.

[0195] Industrial applications The sealing sheet of the present invention is useful in sealing electronic devices, such as organic EL devices, solar cells, sensor devices, touch panels with conductive substrates, etc.

Claims

1. A sealing sheet having a laminated structure comprising a support and a sealing layer, wherein, The sealing layer consists of a first moisture-absorbing layer and a second moisture-absorbing layer. The first moisture-absorbing layer is in direct contact with the second moisture-absorbing layer. The first absorbent layer comprises the following components (A) and (B): (A) Olefin polymers, and (B) Semi-calcined hydrotalcite; and The second absorbent layer contains the following components (C) and (D): (C) Olefin polymers, and (D) Calcium oxide, Component (A) in the first absorbent layer comprises: olefin polymers having anhydride groups and / or carboxyl groups, and olefin polymers having epoxy groups. Component (C) in the second moisture-absorbing layer comprises olefin polymers having anhydride and / or carboxyl groups, and the median particle size of component (D) in the second moisture-absorbing layer is 1–300 nm. The content of component (D) is 10-80% by mass relative to the entire second absorbent layer.

2. The sealing sheet according to claim 1, wherein, The median particle size of component (D) is 5 nm to 250 nm.

3. The sealing sheet according to claim 1, wherein, The olefin polymer containing an anhydride group and / or carboxyl group in component (C) of the second moisture-absorbing layer is an olefin polymer containing an anhydride group.

4. The sealing sheet according to claim 1, wherein, The (C) component in the second absorbent layer contains olefin polymers with epoxy groups.

5. The sealing sheet according to claim 4, wherein, The olefin polymers containing anhydride and / or carboxyl groups in component (C) of the second absorbent layer form a cross-linked structure with olefin polymers containing epoxy groups.

6. The sealing sheet according to any one of claims 1 to 5, wherein, (B) The content of component B is 10 to 80% by mass relative to the first absorbent layer as a whole.

7. The sealing sheet according to claim 6, wherein, (B) The content of component B is 15 to 75% by mass relative to the first absorbent layer as a whole.

8. The sealing sheet according to claim 1, wherein, The content of component (D) is 15-75% by mass relative to the entire second absorbent layer.

9. The sealing sheet according to claim 1, wherein, The olefin polymer containing an anhydride group and / or carboxyl group in component (A) of the first moisture-absorbing layer is an olefin polymer containing an anhydride group.

10. The sealing sheet according to claim 1, wherein, The olefin polymers containing anhydride and / or carboxyl groups in component (A) of the first hygroscopic layer form a cross-linked structure with olefin polymers containing epoxy groups.

11. The sealing sheet according to any one of claims 1 to 5, wherein, One or both of component (A) in the first moisture-absorbing layer and component (C) in the second moisture-absorbing layer contain liquid olefin polymers.

12. The sealing sheet according to any one of claims 1 to 5, wherein, One or both of the first and second moisture-absorbing layers contain an adhesive agent.

13. The sealing sheet according to any one of claims 1 to 5, wherein, The thickness of the sealing layer is 3–200 μm.

14. The sealing sheet according to claim 13, wherein, The thickness of the sealing layer is 3–150 μm.

15. The sealing sheet according to any one of claims 1 to 5, wherein, The ratio of the thickness of the second moisture-absorbing layer to the thickness of the first moisture-absorbing layer, i.e., the ratio of the thickness of the second moisture-absorbing layer to the thickness of the first moisture-absorbing layer, is 0.05 to 2.

0.

16. The sealing sheet according to claim 15, wherein, The ratio of the thickness of the second moisture-absorbing layer to the thickness of the first moisture-absorbing layer, i.e., the ratio of the thickness of the second moisture-absorbing layer to the thickness of the first moisture-absorbing layer, is 0.05 to 1.

5.

17. The sealing sheet according to any one of claims 1 to 5, wherein, The haze of the sealing layer is less than 60%.

18. The sealing sheet according to claim 17, wherein, The haze of the sealing layer is below 40%.

19. An electronic device comprising a sealing layer formed from a sealing sheet according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Resin composition for sealing

    WO2017057708A1

  • Sealer composition having double layer for reinforcing the steel plate

    KR1020130054070A

  • Sealing resin composition

    WO2021065973A1